The Afterlives of Nicholas Love. (22nd December 2017) - Smith, Jeremy J.
ABSTRACT: In recent years, historical pragmatics has extended its range to engage not only with lexical and grammatical features but also with other aspects of written text not generally considered 'linguistic'. One such area is punctuation. This article investigates punctuation practices in copies, both manuscript and in print, of an important late medieval English text, Nicholas Love's Mirror of the Blessed Life of Jesus Christ, one of the most widely circulated English texts of the fifteenth and early sixteenth centuries. It shows how changes in punctuation mirror wider social changes in a crucial period of cultural formation.